The Simulation of Artificial Sensory Nerves System to Sense Intestinal Contents with Reflective IR Sensor - Hanhui, Lin; Cai, Ken; Li, Jianguo; Zeng, ZhaoFeng (International Journal of Online and Biomedical Engineering (iJOE), 2015)
Patients who has fecal incontinence suffer physical and mental painfulness because they can neither actively control any forms of defecation nor detect the state of intestinal contents. It is significantly meaningful to study artificial anus sphincter with “artificial sensory nerves”. In this paper, reflective infrared (IR) sensor, with different responses to the solutes, can simulate the sensory nerves to detect intestinal contents to distinguish different solutes according to the voltage values of the different reflective responses to the IR of the solutes. The study meets the requirements as expected because the outcome shows that the voltage signals of different solution differ dramatically which can detect whether there are any intestinal contents and distinguish the states of them. It turns out to be an effective method that the reflective IR sensor can simulate the sensory nerves to sense intestinal contents.